Double‐Negative Mechanical Metamaterials Displaying Simultaneous Negative Stiffness and Negative Poisson's Ratio Properties. Issue 46 (26th October 2016) - Hewage, Trishan A. M.; Alderson, Kim L.; Alderson, Andrew; Scarpa, Fabrizio
Abstract : A scalable mechanical metamaterial simultaneously displaying negative stiffness and negative Poisson's ratio responses is presented. Interlocking hexagonal subunit assemblies containing 3 alternative embedded negative stiffness (NS) element types display Poisson's ratio values of –1 and NS values over two orders of magnitude (–1.4 N mm −1 to –160 N mm −1 ), in good agreement with model predictions.